KESETARAAN GENDER DITINJAU DARI PERKEMBANGAN HUKUM WARIS BAGI PEREMPUAN BALI - Ida Ayu Putu Sri Astiti Padmawati, SH.,MH.; Ida Bagus Sudarma Putra (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Balinese society with a patrilineal kinship system (in Bali it is better known as purusa or kapurusa), is always interesting to provide material for discussion, especially when it is associated with the position of women in the family and society. The existence of Balinese women, in various aspects of life, is felt to be in a position that does not reflect gender equality and justice. The Kapusa system adopted is